Long-term development of performance, physiological, and training characteristics in a world-class female biathlete - Solli, G. S.; Flom, A. H.; Talsnes, R. K. (Frontiers in Sports and Active Living, 2023)
Purpose: The purpose of this study is to investigate the long-term development of performance, physiological, and training characteristics in a world-class female biathlete, with emphasis on differences between junior and senior athlete seasons.